Postskriptum Peter Szondi : Theorie des Dramas seit 1956 - Bremer, Kai (Lettre, 2017)
How is drama related to its potential enactment - and is the writer really absent in his or her play? Kai Bremer explores the development of drama since Brecht based on Peter Szondi's "Theory of Modern Drama."